Performance appraisal practice in TM Melaka Berhad / Mohd Izzuddin Ibrahim and Mustaqim Mohd Wazir - Ibrahim, Mohd Izzuddin; Mohd Wazir, Mustaqim (Faculty of Administrative Science and Policy Studies, 2012)
Performance management has developed from a very operational focus to a more strategically oriented concept, i.e. where it plays an integral role in the formulation and implementation of strategy (Scott-Lennon, 1995). It is this strategic impetus which differentiates it from performance appraisal. Performance management seeks to align a number of processes (e.g. performance related pay systems) with corporate objectives (McKenna and Beech, 2008). Theoretically it involves a shared process between managers, individuals and teams where goals are agreed and jointly reviewed. Further, corporate, divisional, departmental, team and individual objectives should all be integrated. Performance appraisal is a crucial element of the performance management process, involving a formal review of individual performance. It is contended that performance management represents possibly the greatest opportunity for a human resource (HR) system to make a telling contribution to organizational performance (Sparrow and Hiltrop, 1994). It represents a system that can inform how the firm's human resources contribute to the organization’s strategic objectives. Unfortunately the extent to which it is an effective and useful system in practice remains open to question. Yet, this research has resulted in very few specific recommendations about designing and implementing appraisal and performance management systems whose goal is performance improvement. The researchers believe that a reason for this is that appraisal research became too interested in measurement issues and not interested enough in ways to improve performance, although some recent trends in the area have begun moving the field in the right direction. The researchers review these trends and their genesis, and propose a motivational framework as a means of integrating what the researchers have learned and generating proposals for future research that focus on employees’ performance improvement.